Between Economic Burden and Cultural Dignity: Belis in the Marital Custom of the NTT Society - Rodliyah, Siti; Purwasito, Andrik; Sudardi, Bani; Abdullah, Wakit (Universitas Negeri Semarang, 2017)
The indigenous marital system giving belis Ã¢â‚¬Ëœbride priceÃ¢â‚¬â„¢ practiced by the East Nusa Tenggara (NTT), Indonesia, is one of the Nusantara marital custom phenomena thatÃ‚Â today has developed and raised issues of both pros and cons which deserves critical scrutiny from Cultural studies and Anthropological perspective. Both perspectives facilitate the critical standpoint of the NTT societyÃ¢â‚¬â„¢s mindset summarized in the cultural or customary marriage rules requiring a marriage with belis. This study revealed that in the attitude towards belis, the East Nusa Tenggara women agreed and taken for granted the construction of their reality and power production through various discourses. Current practice of belis raises the economic capitalism up to the identity contestations. Lately, the essence and value of belis have changed and are likely to be more commercial. Even some may view it as mere a symbol and customary fixtures, such as in the region of Lamaholot imposing the elephant tusks, and the Allor society with their Moko as the payment methods of belis.Ã‚Â Belis has left biggest challenge for the communities who are not able to afford higher bride-price objects, this consequently lead to a more emerging unlawful marriages as a resistance against the unresolved poverty problems.